Caregivers' Lived Experiences in Providing Care for Vegetative Patients: A Phenomenological Inquiry - Roselyn Bulauan; Jennifer Anne Arada; Jean Aiza Espiritu; Helen Villaraza (Camarines Sur Polytechnic Colleges, 2023)
The challenges faced by caregivers, encompassing mental, emotional, physical, social, and spiritual dimensions, represent a critical area of study for healthcare professionals aiming to offer comprehensive support. This study, conducted at a Manila tertiary hospital over two weeks in April 2023, utilized an in-depth interview guide to explore the experiences of four diverse caregivers tending to individuals in a vegetative state. Findings revealed four prominent themes: the willingness to assume the caregiver role, lifestyle and social alterations, fear of the unknown, and personal struggles along with coping mechanisms and support systems. The intimate, personal interviews provided a deep understanding of the caregivers' multifaceted challenges. Caring for a loved one in a vegetative state demands substantial emotional and physical tolls, leading to daily anxiety and concern. Recognizing the complexities of their situation and providing the necessary support can significantly alleviate the burdens they face. Moreover, for these caregivers, it becomes a way to reciprocate the love and care previously bestowed upon their loved ones enduring such a condition. This exploration underscores the demanding nature of caring for those in a vegetative state within a familial setting, highlighting the imperative need for holistic support systems and interventions. Understanding the intricacies of caregivers' experiences is pivotal in designing effective strategies to mitigate their challenges and offer the necessary assistance and care.